Transformasi Digital dan Keterbatasan Lembaga dalam Penyiaran Islam: Studi pada Kanal YouTube Masjid Istiqlal TV - Al Fahrizal; Muhamad Iqbal; Khofawati Khoiriyyah; Saepul Saepul (FASTABIQ: JURNAL STUDI ISLAM, 2025)
Masjid Istiqlal TV (MITV), the official YouTube channel of the Istiqlal Mosque, aims to promote Islamic teachings through digital media. However, its content remains conventional and monotonous, failing to engage modern audiences. This study investigates the limited reach of MITV’s content and explores strategies to optimize its digital communication. Employing a qualitative approach with a critical paradigm, data were collected through content observation, YouTube Analytics analysis, and in-depth interviews with the Director of Istiqlal’s Media Development Institute. The findings reveal that 63% of MITV videos document routine religious activities with static production styles and minimal adaptation to audience preferences. Creative limitations are shaped by bureaucratic structures, institutional norms, and a lack of professional digital expertise. Academically, this study contributes to the discourse on digital religion and media logic by highlighting the structural tension between institutional authority and participatory digital culture within state religious institutions. Practically, it recommends transforming content formats, enhancing audience research, and fostering creative collaborations within institutional boundaries to make MITV more dynamic, engaging, and competitive in the contemporary digital da’wah landscape.